Scaling GUI Interaction Log Diversity Enhances Robustness of GUI Agents in AppSight - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 11 peer-reviewed papers addressing the following research question: What is the impact of scaling the diversity of GUI interaction logs in fine-tuning datasets on the robustness of GUI agents against unseen interface layouts in the AppSight benchmark. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 5.8/10. This report is a machine-gen
Machine-generated literature synthesis.